Analysis of Student Satisfaction with the Performance of Lecturers in the Digital Business Study Program at Pelita Bangsa University - Rustianah Rustianah; Rika Nurhidayah; Riski Eko Ardianto; Wachid Hayim (Utan Kayu Publishing, 2025)
The development of tertiary education is currently very rapid, especially as the need for education is very much needed by students, so it is mandatory for all tertiary institutions to really pay attention to the quality of lecturers, which has an impact on the level of satisfaction of students from Pelita Bangsa University's Digital Business study program. This research is classified as quantitative, so the discussion carried out is data obtained from research which is the result of SPSS 25.0 analysis, observation, interviews and questionnaires. The type of sample used was purposive sampling. From the research, the results obtained are that based on SPSS 25.0 data, we can conclude that students who feel satisfied with the performance of Digital Business lecturers with the highest score are Empathy with a total of 30% and the lowest is stable with 12.2%. Then in the quite satisfied category, the highest score is still Empathy with 31.1% and the lowest is 11.1%, namely responsiveness. Dissatisfied category with 2 out of 5 Tangible 64.4 and Responsiveness 35.6%.